Long-Term Outcomes in the Management of Painful Diabetic Neuropathy. (9th January 2017) - Mai, Lauren M.; Clark, A. John; Gordon, Allan S.; Lynch, Mary E.; Morley-Forster, Pat K.; Nathan, Howard; Smyth, Catherine; Stitt, Larry W.; Toth, Cory; Ware, Mark A.; Moulin, Dwight E.
Abstract: Background: Painful diabetic neuropathy (PDN) is a frequent complication of diabetes mellitus. Current treatment recommendations are based on short-term trials, generally of ≤3 months' duration. Limited data are available on the long-term outcomes of this chronic disease. The objective of this study was to determine the long-term clinical effectiveness of the management of chronic PDN at tertiary pain centres. Methods: From a prospective observational cohort study of patients with chronic neuropathic non-cancer pain recruited from seven Canadian tertiary pain centres, 60 patients diagnosed with PDN were identified for analysis. Data were collected according to Initiative on Methods, Measurement, and Pain Assessment in Clinical Trials guidelines including the Brief Pain Inventory. Results: At 12-month follow-up, 37.2% (95% confidence interval [CI], 23.0-53.3) of 43 patients with complete data achieved pain reduction of ≥30%, 51.2% (95% CI, 35.5-66.7) achieved functional improvement with a reduction of ≥1 on the Pain Interference Scale (0-10, Brief Pain Inventory) and 30.2% (95% CI, 17.2-46.1) had achieved both these measures. Symptom management included at least two medication classes in 55.3% and three medication classes in 25.5% (opioids, antidepressants, anticonvulsants). Conclusions: Almost one-third of patients being managed for PDN in a tertiary care setting achieve meaningful improvements in pain and function in the long term. Polypharmacy including analgesic antidepressants and anticonvulsants were the mainstays of effective symptom management. RÉSUMÉ: Résultats à long terme de la prise en charge de la neuropathie diabétique douloureuse. Contexte: La neuropathie diabétique douloureuse (NDD) est une complication fréquente du diabète sucré. Les recommandations de traitement actuelles sont basées sur des essais cliniques à court terme, en général d'une durée de 3 mois ou moins. Il existe peu de données sur les résultats à long terme du traitement de cette maladie chronique. Le but de cette étude était de déterminer l'efficacité clinique à long terme de la prise en charge de la NDD chronique dans des centres tertiaires de traitement de la douleur. Méthodologie: Nous avons analysé les données de 60 patients chez qui un diagnostic de NDD avait été posé. Ces patients ont été identifiés parmi les patients d'une cohorte d'observation prospective de patients atteints de neuropathie chronique non cancéreuse, recrutés dans 7 centres tertiaires canadiens de traitement de la douleur. Les données ont été recueillies selon les lignes directrices Initiative on Methods, Measurement, and Pain Assessment in Clinical Trials incluant le Questionnaire concis sur les douleurs, version courte. Résultats: Au moment du suivi de 12 mois, 37, 2% (intervalle de confiance à 95% [IC] de 23, 0 à 53, 3) parmi les 43 patients dont les données étaient complètes avaient obtenu une diminution de la douleur de 30% ou plus, 51, 2% (IC à 95% de 35, 5 à 66, 7) avaient obtenu une amélioration fonctionnelle avec diminution de 1 ou plus à la Pain Interference Scale (1-10 au Questionnaire concis sur les douleurs, version courte) et 30, 2% (IC à 95% de 17, 2 à 46, 1) avaient obtenu ces deux résultats. Au moins deux classes de médicaments étaient utilisées chez 55, 3% des patients et trois classes de médicaments chez 25, 5% (opiacés, antidépresseurs, anticonvulsivants) pour la gestion des symptômes. Conclusions: Presque le tiers des patients traités pour une NDD dans un centre tertiaire de traitement de la douleur obtiennent des améliorations significatives de la douleur et de la fonction à long terme. La polypharmacie, incluant des analgésiques, des antidépresseurs et des anticonvulsivants, constitue la base du traitement pour une prise en charge efficace des symptômes.